2010
DOI: 10.1186/1471-213x-10-59
|View full text |Cite
|
Sign up to set email alerts
|

Copine A plays a role in the differentiation of stalk cells and the initiation of culmination in Dictyostelium development

Abstract: BackgroundCopines are calcium-dependent phospholipid-binding proteins found in diverse eukaryotic organisms. We are studying the function of copines in Dictyostelium discoideum, a single-celled amoeba that undergoes cell differentiation and morphogenesis to form multicellular fruiting bodies when placed in starvation conditions. Previously, we showed that Dictyostelium cells lacking the copine A (cpnA) gene are not able to complete the developmental cycle, arresting at the slug stage. The aim of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…In a previous study, we found that mixing 5% or more wild‐type cells with cpnA‐ cells was able to rescue this culmination defect and that wild‐type cells within these mixed chimerics were located throughout the slug (Damer et al. 2007; Smith et al. 2010).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In a previous study, we found that mixing 5% or more wild‐type cells with cpnA‐ cells was able to rescue this culmination defect and that wild‐type cells within these mixed chimerics were located throughout the slug (Damer et al. 2007; Smith et al. 2010).…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies on Dictyostelium cells lacking the cpnA gene indicate that cpnA plays a role in regulating aggregation, slug size, and culmination (Damer et al. 2007; Smith et al. 2010).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations